Sensor de temperatura em fibra óptica quasi-distribuído baseado em grades de Bragg - Marques, Rogério da Silva (2015)
Temperature monitoring is a critical activity for the whole oil & gas industry. The challenges involved in crude oil storage at hazardous production sites open opportunities for new sensing systems capable of safely performing dynamic temperature tank profiling. This article presents a corrosion resistant, maneuverable, and intrinsically safe temperature optical sensor based on fiber Bragg grating (FBG). The presented sensor head is based on multiple FBG inscribed in a lengthy single mode fiber. The sensor presents an average thermal sensitivity of 8:82 0:09 pm/°C, resulting in a typical temperature resolution of 0:1 ºC and an average time constant value of 6:25 0:08 s. Polytetrafluoroethylene (PTFE) was proposed as a means of simultaneously isolating the optical fiber from the corrosive environment and avoiding undesirable mechanical tensions over FBGs. PTFE also improves the overall sensor robustness without impairing its handling features. Corrosion and degradation resistance were verified by infrared spectroscopy and scanning electron microscopy along 90 days exposition to high salinity crude oil samples. The developed sensor was tested in a field pilot test, reproducing the operation of an in land crude tank, demonstrating its abilities to dynamically monitor temperature profile.